Genome-wide association study of depression phenotypes in UK Biobank identifies variants in excitatory synaptic pathways - David M. Howard (Nature Portfolio, 2018)
The UK Biobank provides data for three depression-related phenotypes. Here, Howard et al. perform a genome-association study for broad depression, probable major depressive disorder (MDD) and hospital record-coded MDD in up to 322,580 UK Biobank participants which highlights excitatory synaptic pathways.